DIAGNOSTIC FEATURES OF NEUROSONOGRAPHY IN INTRAUTERINE INFECTION IN NEWBORNS (Лучшие интеллектуальные исследования, 2025)
Annotation. In the article are given date 60 newborns with gestation period from 28 to 41 weeks with hypoxic lesion of the CNS of the early period. At all stages of the study and observation of newborns conducted a collection of gynecological, obstetric anamnesis, studied the specifics of the course of pregnancy and childbirth. The early neonatal period was assessed by taking into account the data of gestational age, mass and length of the body at birth, the circumference of the head and stem cells, physiological destruction of the mass of the body, analyzed the state of recurrence of childbirth. The dynamics of the neuropsychological status of the examined children was assessed.